IDENTIFIKASI PERSEBARAN HIDROKARBON PADA KONGLOMERAT FORMASI JATIBARANG MENGGUNAKAN ANALISIS INVERSI AVO (Amplitude Versus Offset) - Retno Septiani; Hernowo Danusaputro; Dimas Pramudito (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
AVO inversion analysis (Amplitude Versus Offset) has been done on DBT-12 field to identify and map the distribution of hydrocarbons in conglomerat layer, Jatibarang formation, northern part of West Java basin. Sensitiv physical parameters to separate conglomerate with other litology (lava) are λ/μ, σ and Vp/Vs. Intercept which is obtained is positive while gradient is negative. AVO anomaly class obtained is IIp can be used as a first indicator content of the fluid is low impedance sand. This reservoir impedance values decrease for the increasing of incidence angle. Besides intercept and gradient AVO attributes which obtained is fluid factor and Poisson reflectivity. Both of these attributes is negative which means changes value of Poisson's ratio is quite large from high to low. Changes in Poisson's Ratio can indicate the existence of a hydrocarbon. Distribution of hydrocarbons DBT-12 on conglomerate layer is northwest - southeast. Keyword : Inversion, AVO, Atributtes, Conglomerat, Hydrocarbon